Discurso reportado em narrativas: a construção colaborativa de histórias na fala-em-interação - Ferla, Joana Restelli (Universidade do Vale do Rio dos Sinos, 2020)
The act of telling stories has lately been the focus of many Academic Studies in Interactional Linguistics (GOFFMAN, 1974; 1981; MANDELBAUM, 1989; 2012; GOODWIN, 2006; HOLT, 2007; 2009) and, especially, in the area of Conversation Analysis (SACKS; SCHEGLOFF; JEFFERSON, 1974). Such studies aimed to investigate how the interactants (re)tell past events, how they organize these reports and how they build different identities for themselves and for others. The studies also investigated the way interactants report their and others’ interactional actions. Reported Speech (henceforth RS), as well as storytelling, has also been the focus of Interactional-Analytic studies, mostly when it happens in storytelling (LARSON, 1978; MAYES, 1990; GOLATO, 2000; HOLT, 2009; ROMAINE; LANGE, 2006). The way it is used and incorporated in storytelling, as well as the way it is constructed, makes the subject a highly interesting topic of discussion and interest. Accordingly, the present study originates from the recognition of the important role RS plays in storytelling, and the interactional and the linguistic interest regarding the roles interactants play while reporting speech. To contribute to the Brazilian interactional linguistic field, by means of the Conversation Analysis and Multimodal Conversation Analysis approach (MONDADA, 2009; 2014; 2018; CRUZ et al, 2019), this study aims to analyze: (1) how RS is introduced; (2) how the interactants implement them in interaction; (3) how RS is co-constructed by the interactants; and (4) the importance of embodied actions in the construction of RS in storytelling. The results indicate that: (a) RS is mainly prefaced by introductory clauses, discourse markers, the combination of both and, also, by the combination of discourse markers and markers of sequentiality. The occurrences of zero-quotatives are less frequent in the data; (b) RS works as an exemplifier of actions done by the own or other interactants — in a previous or in a hypothetical moment —, to assess an action, to demonstrate the storytelling sequentiality, to build dialogue and formulations, etc; (c) RS is co constructed through interactants’ formulation attempts regarding the necessity of collaboration and through repair initiations; and (d) it is used in order to instantiate an occurrence and/or action that occurred originally.
Keywords: Discurso reportado; Narrativas; Análise da Conversa; Fala-em-interação; Storytelling; Reported peech; Conversation analysis; Talk-in- interaction